PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA PELAJARAN BAHASA INDONESIA SISWA KELAS III SD NEGERI 6 DAWUHAN TAHUN PELAJARAN 2017/2018 - Nur Hayati; Nani Farah Fasica (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Descriptive text has described object by using words. The description objects included person, places, events etc. The writer determined it by smell, and situation according to the object, the problem in this researh namely the students of third grade at SDN 6 Dawuhan having some problems in writing descriptive text. The students felt difficulty in choosing the word dictions. The research problem were 1) How to implement pictures series to third grade students at Bahasa Lesson in SDN 6 Dawuhan Situbondo academic year 2017/ 2018 2). Did the Implementation of pictures series improve the descriptive writing skills at third grade students in SDN 6 Dawuhan academic year 2017/2018. The type of this research is Classroom Action Research (CAR). The subjects of this research are students of Class III of State Elementary School 6 Dawuhan with 24 students, cycle is done as many as II cycle. The result of writing ability description of third grade students of SD Negeri 6 Dawuhan increased. In the implementation of pre cycle the average score of students is 43 with the category of "Less Good" after the first cycle of the student's average score increased to 56.7 with the category of "Good Enough" while in the second cycle the average value of students improved is 77, 7 with the category "Good". The percentage of students who achieved the value of Minimum Score Passing Grade (65) increased, the implementation of prasiklus which reached the value of Minimum Score Passing Grade only 4 students and who did not reach the value of Minimum Score Passing Grade as many as 20 students. While the first cycle that reached the value of Minimum Score Passing Grade that is 10 students and who did not reach the value of Minimum Score Passing Grade as many as 14 students. In the second cycle, the Minimum Score Passing Grade score is 24 students